Inflation and Output Comovement in the Euro Area : Love at Second Sight? - Andrle, Michal; Bruha, Jan.; Solmaz, Serhat (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses comovement between inflation and output in the euro area. The strength of the comovement may not be apparent at first sight, but is clear at business cycle frequencies. Our results suggest that at business cycle frequency, the output and core inflation comovement is high and stable, and that inflation lags the cycle in output with roughly half of its variance. The strong relationship of output and inflation hints at the importance of demand shocks for the euro area business cycle.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States